1993
DOI: 10.1095/biolreprod49.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Concentration during Maturation and after Fertilization in Pig Oocytes: Relevance to the Ability of Oocytes to Form Male Pronucleus1

Abstract: The present study examined the kinetics of glutathione (GSH) concentration during maturation and after fertilization in pig oocytes and its relevance to the ability of pig oocytes to form a male pronucleus after in vitro fertilization. The GSH concentration was significantly higher in pig oocytes matured in Waymouth medium than in pig oocytes matured in either modified (m) TCM-199 or mTLP media. The addition of 0.04-0.57 mM cysteine (CySH) to mTLP significantly increased both the GSH concentrations in oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
229
4
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(248 citation statements)
references
References 32 publications
11
229
4
4
Order By: Relevance
“…Because BDNF treatment enhanced oocyte glutathione content, these findings suggest that BDNF could play a role in successful fertilization. Our data are consistent with earlier studies showing a correlation between glutathione levels in mature pig oocytes and their ability to form male pronuclei after fertilization (19). Thus, ovarian BDNF could activate separate downstream pathways in the oocyte to facilitate nuclear maturation (first polar body extrusion) as well as fertilization (glutathione content) and early embryo development.…”
Section: Discussionsupporting
confidence: 93%
“…Because BDNF treatment enhanced oocyte glutathione content, these findings suggest that BDNF could play a role in successful fertilization. Our data are consistent with earlier studies showing a correlation between glutathione levels in mature pig oocytes and their ability to form male pronuclei after fertilization (19). Thus, ovarian BDNF could activate separate downstream pathways in the oocyte to facilitate nuclear maturation (first polar body extrusion) as well as fertilization (glutathione content) and early embryo development.…”
Section: Discussionsupporting
confidence: 93%
“…With BCB+ oocytes, the difference between the percentage of cleaved embryos (45.3%) and the percentage of 2PN oocytes (39.7%) was reduced which suggests a lower number of haploid embryos obtained with BCB+ oocytes matured with cysteamine. Several authors have found an effect of intracytoplasmic GSH levels on MPN formation [15,16,28,31,33,34]. In our study we observed significantly higher percentages of MPN in oocytes matured with cysteamine compared to the control group (80.3 vs. 61.5%, respectively).…”
Section: Discussionsupporting
confidence: 59%
“…In oocytes, intracytoplasmic GSH participates in the transformation of the fertilising sperm head in the male pronucleus. It is believed that at fertilisation, a high intracellular GSH content is needed for the transformation of the disulphide-stabilised sperm nucleus into the male pronucleus [30,31]. Indeed, the decrease in intracellular GSH of mouse oocytes impairs the decondensation of the sperm nucleus [32].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly interesting is the fact that the addition of CYS to IVM medium in pig oocytes results in increased glutathione (GSH, a derivative product of CYS) synthesis by the pig oocytes (Yoshida et al 1993), enhancing in vitro development after IVF (Grupen et al 1995;Kishida et al 2004). In addition, GSH synthesis during oocyte maturation is an important factor for promoting their ability to form a MPN after IVF (Yoshida et al 1993;Sawai et al 1997), and GSH is known to be a prerequisite to ensure sperm chromatin decondensation (Perreault et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GSH synthesis during oocyte maturation is an important factor for promoting their ability to form a MPN after IVF (Yoshida et al 1993;Sawai et al 1997), and GSH is known to be a prerequisite to ensure sperm chromatin decondensation (Perreault et al 1984). Accordingly, porcine IVM media have routinely been supplemented with CYS.…”
Section: Introductionmentioning
confidence: 99%